A Symbolic Approach for the Synthesis of Planar Four bar Linkage Function Generator - 徐礼钜; 林光春 (Jixie chuandong)
The Symbolic solutions to the synthesis problem of planar four bar linkage function generator are proposed based on Wu Elimination and computer symbolic manipulating technique in this paper.A set of nonlinear polynomial equations are transformed into a set of equivalent triangularization equations by using the following operations:ordering of variables,grouping,reduction,forming basic set,and finding remainder terms etc.The closed form solutions of original equations are obtained.